IMPLEMENTASI PROGRAM KAMPUNG RAMAH ANAK (KRA) DALAM PEMENUHAN HAK ANAK DI KAMPUNG KARANGANYAR RW 16 KOTA YOGYAKARTA - Fariza Widy Athia; Ari Subowo; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Children as the next generation of the nation have the right to fulfill their rights. The implementation of the Child-Friendly Village Program is one of the CFC policy strategies that aimed to create an environment that ensures the fulfillment of children's rights at the village level by all stakeholders. However, this program still not perfect in its implementation, there are still several aspects that obstruct the implementation process. The purpose of this research was to describe the implementation of the KRA program in fulfilling children's rights in Karanganyar Village, RW 16 and to find out the supporting and inhibiting factors. This research used the theory of child rights concept and implementation of Van Meter and Van Horn by looking at the size and objectives, resources, characteristics of implementing agents, disposition of implementers, communication, and socio-political-economic environment. This research used descriptive qualitative method with case study approach. The results showed that implementation of the KRA program was still not optimal, because there were problems in fulfillment the five clusters of children’s rights. In conclusion, the implementation of KRA is supported by variables of size and purpose, quality of human resources, characteristics of implementing agents, disposition of implementers, and socio-politicaleconomic environment. Meanwhile, the obstacle variables of this program are the quantity of human resources, budgetary resources, and communication of the implementers are obstacles. This research recommends an increase in the quantity of human resources, budget allocation from the sub-district, regeneration of the management of the task force, improving the quality of communication for implementers, and increasing guidance from the sub-district as the KRA coach